Safety of individualized herbal medicine for dysmenorrhea: pharmacovigilance from South Korea’s national pilot - Park, Minjung; Kim, Yongjoo; Yoon, Nan-He; Bae, Kyeore; Yi, Junhyeok; Kim, Sujin (Frontiers in Pharmacology, 2026)
BackgroundIn 2020, South Korea’s National Health Insurance (NHI) began reimbursing individually prescribed herbal medicine decoctions (HMDs) for dysmenorrhea, highlighting the need for robust post-coverage safety monitoring using national claims data.ObjectiveTo evaluate the safety of reimbursed HMDs for dysmenorrhea and demonstrate a claims-based pharmacovigilance approach to inform benefit management and clinical guideline integration.MethodsA retrospective cohort study was conducted using the Health Insurance Review & Assessment (HIRA) national claims database from 2015 to 2022. HMD users were coarsened-exact-matched to nonusers on sociodemographic and clinical characteristics. Difference-in-differences models compared pre- and post-coverage outcomes at 1, 3, 6, and 11 months. Primary outcomes were hepatotoxicity and renal failure; secondary outcomes included allergic reactions, emergency department visits and hospitalizations.ResultsThe matched cohort comprised 8,989 HMD users and 8,989 nonusers. Reimbursed HMDs were not associated with increased risk of severe adverse events at any time point. At 3 months, DID estimates were −2.6 (95% CI −411.8, 406.6) for hepatotoxicity and −7.2 (95% CI −402.3, 388.0) for renal failure, with consistent safety patterns across endpoints and sensitivity analyses.ConclusionCoverage of individually prescribed HMDs under South Korea’s NHI system was not associated with elevated serious safety risks for dysmenorrhea. These findings support continued reimbursement and provide a scalable template for claims-based pharmacovigilance using standardized endpoints, routine signal detection, and feedback to benefit design and clinical practice.